(untitled) (Journal of Economic Research & Business Administration, 2015)
Due to the increasing competition in the educational environment in Kazakhstan and the world, sharply raises the question of efficient management of educational facilities, particularly in higher education. In this connection it is necessary to analyze the key areas of the university through the use of tools of risk management. As a qualitative analysis involves the identification of the most vulnerable places and also in the future development of measures to mitigate the possible negative effects, the techniques used in risk management are the most appropriate for the task. In addition, this article covers the importance of risk management in the enterprises of the educational environment, particularly in higher education. It also discusses the basic tools and mechanisms for risk management, which may apply to universities in order to reduce the negative consequences of wrong management decisions.